Effect of humic acids on the activity of pure and mixed methanogenic cultures. (April 2017) - Khadem, Ahmad F.; Azman, Samet; Plugge, Caroline M.; Zeeman, Grietje; van Lier, Jules B.; Stams, Alfons J.M.
Abstract: The impact of humic acid (HA) on methanogenic activity was investigated. Methanogenic crushed granular sludge and pure cultures of mesophilic methanogens were incubated in batch cultures with HA. Initial methane production rates and substrate consumption rates were quantified. In the presence of 1 kg m −3  HA, the methane production rate of all hydrogenotrophic methanogens was inhibited by more than 75%, except Methanospirillum hungatei that was not inhibited up to 5 kg m −3  HA. The acetoclastic Methanosarcina barkeri was completely inhibited by HA ≥1 kg m −3 . However, Methanosaeta concilii was only slightly affected by HA up to 3 kg m −3 . When methanogenic granular sludge was incubated with HA, the specific methanogenic activity (SMA) tests showed less inhibition, when compared to the pure cultures of methanogens. The SMA test with H2 /CO2, formate and acetate showed reduced initial methane production rate of 42%, 23% and 40%, respectively. Differences in HA susceptibility were explained by differences in cell wall structure. Highlights: Most of the tested hydrogenotrophic methanogens were inhibited by humic acid (HA). M. concilii was not affected by HA whereas, M. barkeri was severely affected by HA. The inhibitory effect seems to be linked to the cell wall structure of methanogens. Anaerobic sludge was less affected by HA, but less methane production was observed.